The comparison of biomechanics of kayak paddling between para-kayakers and elite able-bodied kayakers: a pilot study - Kono, Y.; Sakamitsu, T.; Sasadai, J.; Yamamoto, M.; Okamoto, K.; Ushio, K.; Mikami, Y.; Kimura, H.; Adachi, N. (Sport Sciences for Health, 2021)
Purpose Understanding the kinematics of the upper extremity during kayak paddling is important for both performance and injury prevention. However, there is a lack of information on scapular and shoulder kinematics in para-kayakers who have additional impairments. This study aimed to clarify the biomechanics of kayak paddling in para-kayakers.